NIA-Shaheen (CIM-04-10): A high-yielding, drought-tolerant wheat variety - Arain,Saima Mir (2021)
Abstract The wheat variety NIA-Shaheen (CIM-04-10) has high grain yield and modern plant architecture. It has wide adaptability, increased tiller production, bold grains, high starch and protein content, and good tolerance to disease and environmental stresses, particularly water stress. NIA-Shaheen has high yield potential (7184 kg ha-1).